2005
DOI: 10.1073/pnas.0409174102
|View full text |Cite
|
Sign up to set email alerts
|

Positive affect and health-related neuroendocrine, cardiovascular, and inflammatory processes

Abstract: Negative affective states such as depression are associated with premature mortality and increased risk of coronary heart disease, type 2 diabetes, and disability. It has been suggested that positive affective states are protective, but the pathways through which such effects might be mediated are poorly understood. Here we show that positive affect in middle-aged men and women is associated with reduced neuroendocrine, inflammatory, and cardiovascular activity. Positive affect was assessed by aggregating mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
459
1
13

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 620 publications
(516 citation statements)
references
References 41 publications
30
459
1
13
Order By: Relevance
“…Recent results from Steptoe and colleagues (Steptoe, Wardle, & Marmot, 2005;Strike, Wardle, & Steptoe, 2004) demonstrate the importance of such data. The authors found a relationship between inflammatory stimulation and negative mood, while temporary PA was inversely related to cortisol and heart rate (HR).…”
mentioning
confidence: 92%
“…Recent results from Steptoe and colleagues (Steptoe, Wardle, & Marmot, 2005;Strike, Wardle, & Steptoe, 2004) demonstrate the importance of such data. The authors found a relationship between inflammatory stimulation and negative mood, while temporary PA was inversely related to cortisol and heart rate (HR).…”
mentioning
confidence: 92%
“…In contrast, positive affect was not associated with IL-6 in the relocation study of older women, which accounted for risk factors and depressive symptoms (E. M. Friedman et al, 2007). Finally, in a study that measured positive affect through ecological momentary assessment, men and women with low versus high positive affect tended to have greater fibrinogen responses to stress, controlling for age, employment, smoking status, BMI, and distress (Steptoe, Wardle, & Marmot, 2005).…”
Section: Biological Functionmentioning
confidence: 99%
“…34,[268][269][270][271][272][273][274] This is an important consideration because it may be possible to use clinical 109 and public health interventions 92 to reduce this burden, thereby narrowing health disparities. Second, social and economic stresses lead to a biological wear and tear, or allostatic stress response, [275][276][277][278][279][280] involving a number of pathways, including stimulation of stress hormones, [280][281][282] inflammation, 283 endothelial dysfunction, thrombosis, vascular hyperreactivity, 270,274,[284][285][286][287] and metabolic disturbances. 270,285,288,289 Third, the effects of socioeconomic disadvantage in utero and in early childhood have long-term anatomical and physiological effects that lead to CVD in adulthood.…”
Section: Biological Mechanismsmentioning
confidence: 99%